Effects of dietary and aqueous zinc on subcellular accumulation and feeding rates of mayflies - Cadmus, Peter, author; Clements, William H. (William Henry), 1954-, advisor; Vieira, Nicole K. M., committee member; Kondratieff, B. C. (Boris C.), committee member; Myrick, Christopher A., committee member (Colorado State University. Libraries, 2011)
Although laboratory toxicity tests have shown that mayflies (Ephemeroptera) are highly tolerant to aqueous Zn exposure, field biomonitoring studies have shown marked decreases in mayfly abundance at relatively low concentrations of metals. Laboratory testing methodologies used for developing water quality standards rely solely on aqueous exposure and often focus on lethal endpoints. In reality, organisms in the field experience chronic exposures to metals through both aqueous and dietary pathways. To investigate the relative importance of dietary metals exposure, I conducted laboratory toxicity tests where the mayflies Epeorus albertae and Ameletus sp. were exposed to aqueous (0, 800, 1600 µg/l) and dietary (722 µg/g vs.104 µg/g) concentrations of zinc. Additional aqueous-only trials (0, 800,1600, 3200, 6400 and 12800 µg/l ) were ran simultaneously. Subcellular partitioning methods were employed to detect differences in how mayflies compartmentalized dietary and aqueous Zn exposure. Results were compared to zinc partitioning in organisms collected across a gradient of Zn-contaminated sites in the upper Arkansas River near Leadville, Colorado. Diet was found to significantly influence both total accumulation of Zn and distribution in subcellular fractions in both mayfly genera. Organisms receiving both dietary and aqueous exposure accumulated significantly more Zn than did organisms exposed to only aqueous Zn. Diet also significantly affected feeding behavior and molting frequency. Ameletus fed significantly less on algae with high levels of Zn than algae with low levels of Zn. These findings suggest that traditional laboratory toxicity tests used in establishing water quality criteria significantly under-represent the potential for accumulation of metals and sublethal effects in the field. Tissue concentrations of Zn in Ameletus and Epeorus after 10 day laboratory exposures were well below those in organisms collected from the Arkansas River, despite lower aqueous concentrations in the field. Addition of dietary exposure improved the realism of our laboratory toxicity tests; however, this alone will not make laboratory tests as sensitive as field studies. These differences in metal uptake between laboratory and field studies suggest that field biocriteria, such as population densities of sensitive mayflies, may be more sensitive and ecologically relevant indicators of stress and recovery in mine-impacted rivers.
Keywords: algae periphyton; aquatic insects; dietary exposure; feeding rates; subcellular fractionation; subcellular zinc accumulation